First record of helminths parasitizing Vanellus chilensis (Aves, Charadriiformes) in Acre state, southwestern Brazilian Amazon - Leandro Siqueira de SOUZA; Leilandio Siqueira De SOUZA; Edson GUILHERME; Francisco Glauco de Araújo SANTOS (Acta Amazonica, 2021)
ABSTRACT The southern lapwing, Vanellus chilensis, is a bird frequently seen in most of Brazil. Although it is widely distributed in other Brazilian biomes, including some parts of the Brazilian Amazon, it has only been recorded in the western Amazonian state of Acre since 2000. We report the presence of intestinal parasites in individuals of V. chilensis from the Cazumbá-Iracema Extractive Reserve in Acre through a coproparasitological analysis. Seven of the nine sampled individuals were parasitized. We observed larvae of Strongyloides sp. (28.5% of the samples), and eggs of Ascaridia sp. (28.5%), Ancylostoma sp. (14.2%), and Choanotaenia sp. (42.8%). These parasites are reported for the first time parasitizing V. chilensis in Brazil. The parasitized birds may act as reservoirs and were recorded in a peridomicile area, which may facilitate their contact with domestic birds.